Penerapan Metode Trend Moment Untuk Prediksi Permintaan Telur Ayam - Putri Wulandari; Fauriatun Helmiah; Rohminatin Rohminatin (Building of Informatics, Technology and Science (BITS), 2022)
CV. Bintang Ternak Hessa Air Genting is one of the livestock companies engaged in the distribution and warehouse of chicken egg products, which is located in Hessa Air Genting Village, Asahan Regency. Based on the results of research and interviews conducted by researchers at CV. Bintang Ternak Hessa Air Genting, a problem that often occurs in the company is that there is often a shortage or accumulation of chicken egg products to be marketed, not in accordance with the number of requests from consumers. The purpose of this study is to apply the Trend Moment method to predict the number of Chicken Egg Demand in CV. Cattle Star Hessa Air Genting in the next few months based on the type of egg, namely A+, A, B, C, D, and E